The Relationship Between Depressive Symptoms and Music Preferences - Valerjev, Pavle; Delimar, Luka Marija (24th Psychology Days in Zadar: Book of Selected Proceedings, 2026)
Music is important because it can influence emotions and mood and promote social relationships. However, the question of what determines a person-s music preferences, particularly in relation to mental health problems such as anxiety and depression, remains under-researched, despite the prevalence of these problems and their impact on daily life. The aim of this study was to investigate the relationship between depressive symptoms and preferences for five music preference dimensions: Intense, Classical, Contemporary, Jazzy, and Unpretentious. These five music preference dimensions comprised 17 music genres, with each music genre being categorised into the corresponding music preference dimension. The study comprised two phases: an online (n=101) and a laboratory measurement of music preferences (n=43). The participants first completed a Depression subscale (DASS-O) and rated their preferences for 17 music genres in an online survey. In the laboratory phase, a subgroup of participants from the first phase rated audio recordings of 34 music clips representing 17 music genres. In both phases of the study, depressive symptoms were positively associated with Intense music, suggesting that individuals with higher depression scores have a greater preference for Intense music (e.g., heavy metal, rock). No significant correlations were found between depressive symptoms and the other four dimensions of music preference. In addition, the participants’ ratings of the music genres which they rated online differed significantly from their ratings after listening to music clips, with the participants expressing a greater preference for Classical, Intense, Jazzy, and Unpretentious music preference dimensions after listening. Gender differences were found, with men preferring Intense music and women preferring Unpretentious music. The correlation between depressive symptoms and a preference for Intense music support the assumption that music preferences, particularly Intense music genres, may reflect emotional states such as depression. The study suggests that music may play a role in understanding and coping with depressive symptoms, which in turn has implications for future research and therapeutic interventions.